The Pragmatic Role of Implicature and Irony in Media Discourse: A Comparative Study - Bekberganov Avazbek; Ikramova Sevara; Bekberganova Khilola (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines the role of implicit communication and irony in media speech acts, and it takes different language and culture perspectives. There are some main concepts taken from pragmatic theory, and these include the concept of implying things during speech, as described by Grice, and there have been developments on how to analyze irony. In this article, the newspaper headlines are selected from different linguistic and cultural milieus, which demonstrate the use of implicatures and ironies. They are employed as pragmatic means to state judgment, criticism, or political stance, even when the apparent purpose seems to be reporting the news. The results reveal both the similarities and differences in how these meanings are constructed, largely driven by cultural norms, journalistic principles, and audience expectations. In conclusion, the article contributes vital concepts to the field of media pragmatics in highlighting the importance of implicit messages in media messages.